Macrophage activation syndrome associated with hepatitis a virus in a child with systemic onset juvenile idiopathic arthritis: A case report (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Macrophage Activation Syndrome (MAS) is a rare but a grave complication of systemic onset juvenile idiopathic arthritis (SOJIA). It occurs as a result of immune dysfunction of macrophages and T lymphocyte. A twelve-year old boy diagnosed case of SOJIA presented with high grade fever, diffuse abdominal pain, vomiting and jaundice. He had high ALT, abnormal coagulation profile and Anti HA V IgM was positive. He had also high ferritin and triglyceride level which were very much suggestive for MAS. Infection especially Epstein Barr Virus, Herpes viruses and drugs are the common triggers for the development of MAS in association with SOJIA patients. MAS associated with hepatitis A virus are very rare. Only a few case reports are available in the literature. Considering its rarity and grave prognosis we are reporting a case of hepatitis A associated Macrophages Activation Syndrome in a systemic onset juvenile idiopathic arthritis.